Hydrogel-based microneedles for transdermal drug delivery and biosensing - Zheng, Mengjia (Nanyang Technological University, 2020)
The microneedle (MN) technology captures great attention because of its effective and patient-friendly manners, which significantly improve patient compliance for long-term and frequent applications. In such applications, the materials of MNs cannot avoid contacting skin tissue and sometimes even for a long duration exposure. The hydrogel-based materials are considered to closely simulate the natural tissues for good safety. In this light, the hydrogel polymer-based MN platforms are proposed in this thesis. Briefly, the transdermal biosensing platforms were developed based on the different strategies: 1. “out-patch” delivery of sensing probes; and 2. “in-patch” extraction and analysis of extracted skin interstitial fluids. The above two platforms were applied for monitoring the localized skin abnormality (i.e. scar), and the systemic physiological status (i.e. glucose, and insulin levels) respectively. Moreover, the hydrogel MN platform was applied for transdermal cell delivery which explored the fabrication and deliverable therapeutic species for MN technologies. Taken together, this thesis demonstrated the hydrogel-based MNs for their applications in transdermal biosensing and transdermal cell delivery, which could serve as potential platforms in point-of-care tests and transdermal delivery.